Ambiente comum de dados (CDE) como matriz de um sistema colaborativo para gestão: inventário e divulgação de bens culturais materiais e imateriais - Alexandre Eduardo Fraga Coelho (2024)
This research evaluates the use of HBIM (Historic Building Information Modeling) in the case study of the Acaiaca Building in Belo Horizonte, where this technology was commercially employed, allowing for the analysis of various "a posteriori" practices. The application of this technology covered the processes of design, construction, maintenance, conservation, and restoration, with management supported by a CDE (Common Data Environment). The evaluation of some processes corroborated the opinion of various authors on the need for greater adaptations in software developed for BIM to meet the specificities of HBIM. The main deficiency identified was the difficulty in obtaining a digital model that truly faithfully represents the real model. Some developments were suggested that could improve these tools, based on the analysis of software dedicated to the entertainment and manufacturing industries, which work with meshes and geometric solids. On the other hand, the perception that the CDEs available for BIM could be more easily adapted for HBIM, extending beyond the scope of management, outlined the main objective of the research. This objective consisted of analyzing the potential development of a specific CDE for HBIM that could be integrated with a historical heritage management body, such as IPHAN, allowing, in addition to the management of historic buildings, the integration with other systems of the body for inventory registration, project approval, dissemination of listed assets, among others. In the development of this research, despite the impossibility of comprehensively investigating the various CDEs for BIM available on the market, some of the main technologies in the sector were analyzed, as well as analogous research and IPHAN's initiative with SICG, which aims at integration with HBIM tools. With the use of the CDE, it was concluded that it is not always necessary to model the entire building faithfully. Having the point cloud stored in the CDE and with the possibility of this cloud being classified by clustering several points, the modeling could focus on the sections that would undergo some intervention, eliminating difficulties encountered in obtaining a faithful HBIM model.